Risk assessment of high-lying innominate artery with neck surgery. (4th March 2017) - Cai, Qian; Zhu, Honglei; Yu, Taihui; Huang, Xiaoming; Liang, Faya; Han, Ping; Lin, Peiliang
Abstract: Conclusion: A high-lying innominate artery (the upper edge of the innominate artery across the anterior midline of the trachea located 2 cm above the suprasternal notch), a rare situation, may produce disturbance to related anterior cervical tracheal surgery and even cause serious complications. Objectives: High-lying innominate artery is a high risk factor in anterior cervical tracheal surgery. Pre-operative assessment via imaging technique can help to familiarize the artery and reduce the related disturbance to the surgery. Methods: A total of 829 patients were selected. Cervical computed tomography (CT) examination was conducted before surgery. The distance between the upper edge of the innominate artery across the anterior midline of the trachea and the suprasternal notch was measured. The exposure of innominate arteries in these cases during surgery was recorded. Results: The upper edge of the innominate artery was located above the suprasternal notch in 26.4% (219/829) of patients. The upper edge of the innominate artery across the anterior midline of the trachea was 2 cm above the suprasternal notch in 18 cases, accounting for 2.2% of all cases, and innominate arteries were exposed in 11 cases (61.1%) during surgery.